Meet God Again for the First Time - Paulien, Jon (Review and Heerald Publishing Association, 2003)
Forget everything you've ever heard or thought about the Bible. When the author set aside his training, traditions, and prejudices and read the Bible straight through to see what it really said, it changed his life. Amazed at what he'd missed, he discovered a very different book than the one he thought he knew. Specifically, he discovered God's paterns. He discovered a consistency, a dependability, in God's great saving deeds—the Creation, the Flood, the Exodus, the Exile, and the cross. He discovered that the Bible is about telling and retelling the story of the God of promise and covenant who keeps working toward His ultimate goal—the restoration of Eden. Salvation and worship are not about what we need to do, he discovered, but about what God has done. When Jesus—the new Adam, the new Moses, the new David, the new Israel—